Strategi Mitigasi Konflik Manusia Dan Monyet Yaki (Macaca nigra) Di Cagar Alam Duasudara Dan Taman Wisata Alam Batuputih Kota Bitung - Tandi, Novita; Paputungan, Umar; Walangitan, Hengki Djemie (Sam Ratulangi University, 2023)
This study aims to analyze ecological, socioeconomic and institutional factors affecting the management of conservation areas and analyze conflict mitigation strategies between wildlife and communities around the Duasudara CA and Batuputih TWA areas. This research was conducted from May - December 2022. The research method uses qualitative and quantitative descriptive approaches. Primary data on the collection of strategic issues through focus discussion groups (FGDs) and direct interviews with key informants. Secondary data was obtained from the Tangkoko Long-Term Management Plan (RPJP) document for 2017-2026 and the Regulation of the Minister of Forestry Number P.48 / Menhut-II / 2008 as well as the results of previous research related to the research. The results showed that there are internal and external factors that affect the management of conservation areas, including area status, yaki monkey status, yaki monkey population, land cover, community activities, tourist visits, NGO involvement, community socioeconomic conditions, and regional boundaries. The results of the analysis related to human and monkey yaki conflict mitigation strategies in Duasudara CA and Batuputih TWA Bitung City using the SWOT method show a position in quadrant I, namely supporting an aggressive strategy where the application of conflict mitigation in Duasudara CA and Batuputih TWA is supported by great strength and opportunity and consider the simultaneous ecological, economic and socio-cultural synergy.